2023
DOI: 10.3390/biomedicines11020457
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of SGLT2 Inhibitor Dapagliflozin on Adropin Serum Levels in Men and Women with Type 2 Diabetes Mellitus and Chronic Heart Failure

Abstract: Background: adropin plays a protective role in cardiac remodeling through supporting energy metabolism and water homeostasis and suppressing inflammation. Low circulating levels of adropin were positively associated with the risk of cardiovascular diseases and type 2 diabetes mellitus (T2DM). We hypothesized that sodium–glucose linked transporter 2 (SGLT2) inhibitor dapagliflosin might represent cardiac protective effects in T2DM patients with known chronic HF through the modulation of adropin levels. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
4
1
Order By: Relevance
“…The results of our study showed that the levels of adropin in chronic HF patients with T2DM were lower than in healthy volunteers and T2DN individuals without HF, whereas in other studies [ 31 , 66 ] elevated levels of adropin were detected in HF patients. We, however, suggested that the use of adropin could be practically useful in patients with T2DM and HF regardless of CKD to stratify the patients at risk of CKD and provide continuous monitoring for risk modification during treatment, including a prediction of target organ damages and a response to the therapy.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The results of our study showed that the levels of adropin in chronic HF patients with T2DM were lower than in healthy volunteers and T2DN individuals without HF, whereas in other studies [ 31 , 66 ] elevated levels of adropin were detected in HF patients. We, however, suggested that the use of adropin could be practically useful in patients with T2DM and HF regardless of CKD to stratify the patients at risk of CKD and provide continuous monitoring for risk modification during treatment, including a prediction of target organ damages and a response to the therapy.…”
Section: Discussioncontrasting
confidence: 75%
“…Yet, low levels of adropin were found in patients with acute myocardial infarction [ 64 ] and stable coronary artery disease (CAD) [ 65 ]. In fact, decreased circulating concentrations of adropin in peripheral blood corresponded to a higher risk of T2DM, CAD, and CKD, but not for HF [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the level of serum LA remained unchanged in 2 clinical studies ( 11 , 26 ). In addition, 12 studies could not decide the effect of SGLT2i on cardiac glucose metabolism due to incomplete indicators ( 19 , 21 , 24 , 26 , 27 , 33 , 34 , 38 , 40 , 45 , 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, SGLT2 inhibitors demonstrated their ability to reduce the levels of hepcidin, inflammatory cytokines, such as IL-6, TNF-alpha, CRP and markers of kidney injury, as well as increase the levels of hemoglobin, erythropoietin, serum uric acid, adropin, irisin, and apelin. 19,22,28,34,[44][45][46][47][48] The majority of these studies did not report any correlations between changes in the biomarkers of glomerular/tubular injury, altered glucose and lipid metabolism, adipocyte/skeletal muscle cell dysfunction and changes in UACR, whereas benefits in their changes were closely associated with slower decline in eGFR, for instance in the CREDENCE and DAPA-CKD trials. 19,28 Moreover, SGLT2 inhibitors seem to show improving kidney function independently of their glycemic effects, 49 while they are able to reduce tubular cell glucotoxicity via inhibition of sodium transporters, modulating mitochondrial dysfunction and suppressing local and systemic inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2 inhibitors have been suggested to prevent kidney fibrosis, podocyte injury and apoptosis of glomerular cells by increasing protective adipokine expression, such as adropin, irisin and apelin, which act directly through the activation of Akt/STAT3 and tyrosine protein kinase JAK2 (JAK2)/signal transducer pathways. 34,45,48,51,52 Finally, SGLT2 inhibitors adapt metabolic homeostasis by mediating the activity of NADPH oxidase and transcription factors (nuclear factor-κB and nuclear factor erythroid 2-related factor 2) preventing advanced glycation and autophagy. 51,52 These effects are considered to be crucial in the treatment of patients with either T2DM- or non-T2DM-related CKD who have HF.…”
Section: Discussionmentioning
confidence: 99%